Investigation of microstructure defects in EUROFER97 under He+/Fe3+ dual ion beam irradiation. (May 2018) - Kaiser, B.; Gaganidze, E.; Dethloff, C.; Schwaiger, R.; Brimbal, D.; Payet, M.; Beck, L.; Aktaa, J.
Highlights: Investigation of He and dpa effects in EUROFER97 by irradiation with He/Fe-ions at 330 °C, 400 °C and 500 °C. TEM analysis of the size, density and Burgers vector of dislocation loops as a function of irradiation temperature. Determination of irradiation hardening by means of nanoindentation. Evaluation of a kinetic reaction rate model for helium bubble nucleation and growth. Abstract: Fusion like conditions for reduced activation ferritic/martensitic steels in the first wall are simulated with single Fe 3+ and He + /Fe 3+ dual ion beam irradiation of EUROFER97 at the Jannus laboratory, CEA Saclay, introducing a damage of 16 dpa and a helium content up to 260 appm. The samples are irradiated at temperatures of 330 °C, 400 °C and 500 °C. The quantitative determination of size distribution and density of dislocation loops is obtained using weak-beam dark-field imaging mode. Burgers vectors of a 0 2 〈 111 〉 are observed for the majority of dislocation loops at irradiation temperatures of 330 °C and 400 °C. At 500 °C no dislocation loops are found. The impact of single and dual ion beam irradiation on mechanical properties is determined by means of nanoindentation. An increase in nano-hardness of up to 35% due to irradiation was measured at samples irradiated at 400 °C. A kinetic rate model is applied for the description of nucleation and evolution of helium bubbles and compared with the experimental results. Evaluating the rate model with help of TEM-results for size and density of bubbles indicates the nucleation scheme as the main source for quantitative disagreement between the model and irradiation.